Determinants of the quality of regional government financial reports at the Regional Financial Management Agency (BPKD) of DKI Jakarta Province - Mais, Rimi Gusliana; Hendra, Lim (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2024)
This research delves into the correlation between human resource competency, information technology utilization, and financial accounting system implementation on the integrity of financial statements within the Regional Financial Management Agency (BPKD) of DKI Jakarta Province. Examining the workforce of BPKD DKI Jakarta Province, the study finds that both human resource competency and the application of financial accounting systems significantly enhance the quality of financial statements. Surprisingly, information technology implementation does not yield a discernible impact on financial report quality. These findings underscore the necessity for BPKD DKI Jakarta Province to enhance its employees' technological proficiency to optimize financial statement preparation, aligning with its objectives. Ultimately, the research highlights the multifaceted nature of BPKD DKI Jakarta Province's performance evaluation.